Training on the Utilization of On-Grid and Off-Grid Solar Panels - Hanifati, Sarah Najla; Djaohar, Mochammad; Muksin, Muksin; Malik, Abdul; Monantun, Readysal (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The community engagement activity in the form of training on the utilization of on-grid and off-grid solar panel systems at SMK Madinatul Ilmi, Muara Gembong, intended to enhance the community’s understanding and technical skills in utilizing solar energy. The training was conducted using a participatory approach and hands-on practice. Evaluation was conducted through pre-tests and post-tests to measure the impact of the training. The post-test results showed a significant increase in participants’ knowledge, with the average score rising from 40.67 to 84.67. The N-Gain score indicated an effective improvement, with a value of 77.6. Participants were able to identify the main components and demonstrated the ability to install and maintain solar panel systems. This training also successfully raised community awareness of renewable energy and encouraged initiatives to implement this technology in daily life. The program involved university students as part of the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) program, providing them with practical field experience. This empowerment model can be replicated in other coastal areas with similar characteristics.